PENGALAMAN PEREMPUAN JURNALIS OLAHRAGA DAN MASKULINITAS PELIPUTAN OLAHRAGA - Ratih Cahyani Putri; Diana Teresa Pakasi; Widjajanti Mulyono Santoso (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Integration and efforts to include women journalists are increasing as a result of advocating for a more inclusive media, including in sports desk. However sports journalist broadcasters are limited, as seen from the way women athletes are covered at various levels, the representation of athletes who get the spotlight as well as the focus on sports industry issues that get coverage priority. This literature review uses the scoping literature review method - a literature discussion on women sports journalists - and Bourdieu's framework to understand sports journalism as doxa and its influence on women journalists and other women workers in sports journalism. Experiences and decision making of women journalists were analyzed with the perspective of Gender Psychology based on previous researches from Journalism, Communication, Sports and Media Studies. The literature analysis resulted in a mapping of the various issues faced by women sports journalists, as well as describing the dynamics and identity negotiations that were experienced. The existence of women sports journalists influences the way sports desk works, the issues and focus of their work, their writing styles, and their strategies in the workplace and sports media as institutions. Women sports journalists create a space to work through their daily lives.